A new species of Euconocephalus Karny, 1907 (Orthoptera: Tettigoniidae: Conocephalinae: Copiphorini) from India - Kumar, Hirdesh; Chand, D Suresh; Raghunathan, C; Banerjee, Dhriti (Zootaxa, 2023)
A new species, Euconocephalus narayanpurensis Kumar & Chand sp. nov., from India is described in this paper. The new species is similar to the African species Euconocephalus lineatipes (Bolívar, 1890), but differs from the latter in the smaller size, more acute humeral sinus, the narrowly rounded apex of elytra and convex male last abdominal tergite. A key to the Indian species of Euconocephalus Karny, 1907 is also provided.